Effect of pre-sowing magnetic treatment of seeds with bio- and mineral fertilization on the soybean cultivated in a saline calcareous soil - T. Rashad, Rama; Shaban, Khaled A. H.; Ashmaye, Samia H.; Abd El-Kader, Mona G.; Mahmoud, Awatef A. (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
Bio-farming is an eco-friendly advance that minimizes the required chemical additives for optimizing the quality of crops that their storage is often accompanied by seeds’ components degradation. Magnetic treatment of seed was considered as a promising tool improves germination and growth. This study aims to evaluate the effect of individual and combined application of bio-fertilizers and the N-P-K mineral fertilizers preceded by magnetic treatment of dry and/or water-soaked seeds before sowing on the yield and quality of soybean cultivated in a saline soil.The field experiment was carried out in a split-split plot design with triplicates. The main two factors (F1) were not bio-fertilized and bio-fertilized plots. The sub-factors (F2) were three application rates (A: 50%, B: 75%, and C: 100%) of recommended doses of the three N, P, K fertilizers. The sub-sub factors (F3) were seeds not magnetically treated (NM) and magnetically treated (M). All factors were studied for dry soybean seeds (without soaking) and soaked seeds in magnetically treated water. After harvesting, soil and plant samples were analyzed. The most significant increase in the soybean seed yield (kg ha-1) was by 49.98% for the bio-fertilized magnetized dry seeds at 75% and 100% mineral N-P-K fertilization compared with the NM soaked seeds at 50% N-P-K (A rate) without bio-fertilization. The 75% mineral fertilization significantly increased the protein (%) by 41.69% and decreased the proline (mg g-1dw) by 46.68%. Magnetic treatment of seeds before cultivation and combined bio/mineral N-P-K fertilization reduced the Proline that alleviats the stress conditions.